DISASTER RESILIENCE IN BUILDING CONSTRUCTION THROUGH CONCRETE CASTING METHODS: IMPLICATIONS FOR THE USE OF STRONG COLUMNS AND WEAK BEAMS - Prianto, Kusnul; Pratama, Hariyono Seputro Youngky; Sadjab, Bayu Achil; Palupi, Endah Kinarya (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2021)
The difficulty in obtaining the construction of a strong-beam-weak column building will be encountered during the concrete casting work because in the implementation the beam may be cast using a higher quality concrete than that used for column casting. This has the potential to result in the construction of strong weak-beam columns which should be avoided in earthquake-resistant structures. This study aims to find the most effective concrete casting method that results in the construction of strong-weak beam-columns as intended above. Observations were made on the construction work of a four-story concrete construction building. Analysis by comparing all foundry works whose implementation uses ready mixed concrete made from one vendor, with those using different vendors for each casting of different building structural components. The data used are in the form of compressive strength test results for column casting samples and beam casting samples. From these data, a graph of the compressive strength sample of beam casting is made, then it is compared with the graph of the compressive strength sample of column casting. The results of the study concluded that using different vendors for casting different components of the building has a greater chance of producing a weak beam-strong column structure.